2005
DOI: 10.1097/01.mpg.0000154012.10420.08
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease in Children with Diarrhea Is More Frequent than Previously Suspected

Abstract: CD is common among patients labeled as chronic diarrhea. In this subgroup, gluten-free diet may lead to a significant improvement in symptoms. Routine testing for CD may be indicated in all patients being evaluated for chronic diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
1
15
1
2
Order By: Relevance
“…We found that CD is present in about 9.2% of the patients coming with typical symptoms (12.1% (13/107) of the patients with chronic diarrhea) and 4.0% of those who come with atypical symptoms of malabsorption. Other studies from Iran also reported that CD is the most common cause of chronic nonbloody diarrhea in adults and children, ranging from 6.5% to 19% [15, 16]. These results indicate that classic presentation of malabsorption, specially with chronic diarrhea, is the main presentation of CD in our society.…”
Section: Discussionmentioning
confidence: 65%
“…We found that CD is present in about 9.2% of the patients coming with typical symptoms (12.1% (13/107) of the patients with chronic diarrhea) and 4.0% of those who come with atypical symptoms of malabsorption. Other studies from Iran also reported that CD is the most common cause of chronic nonbloody diarrhea in adults and children, ranging from 6.5% to 19% [15, 16]. These results indicate that classic presentation of malabsorption, specially with chronic diarrhea, is the main presentation of CD in our society.…”
Section: Discussionmentioning
confidence: 65%
“…The true incidence evaluated by a North American study is about 0.5% to 1%, but many, if not most, of studied patients were asymptomatic members of high-risk groups [3, 4]. Recent epidemiological studies performed in North Africa and Asian areas also showed a high rate of CD: 0.53% in Egypt [5], 0.79% in Libya [6], 0.6% in Tunisia [7], 0.88% in Iran [8], 0.6% in Turkey [9], and 0.7% in India [10]. The classic form of CD typically presents in infancy and manifests as failure to thrive, diarrhea, abdominal distention, developmental delay, and, occasionally, severe malnutrition [11, 12], which can lead to a true medical emergency [11].…”
Section: Introductionmentioning
confidence: 99%
“…Как показали недавние эпидемиологи-ческие исследования, проведенные в развиваю-щихся странах, показатели распространенности целиакии в них сопоставимы с европейскими. Например, в Северной Африке они составили 0,53% в Египте, 0,79% в Ливии и 0,6% в Тунисе [21][22][23], на Ближнем Востоке -0,88% в Иране и 0,6% в Турции [24,25], в Индии -0,7% [26].…”
unclassified